PRKACB variants in skeletal disease or adrenocortical hyperplasia: effects on protein kinase A. Issue 11 (November 2020) - Espiard, Stephanie; Drougat, Ludivine; Settas, Nikolaos; Haydar, Sara; Bathon, Kerstin; London, Edra; Levy, Isaac; Faucz, Fabio R; Calebiro, Davide; Bertherat, Jérôme; Li, Dong; Levine, Michael A; et al.
Abstract : Genetic variants in components of the protein kinase A (PKA) enzyme have been associated with various defects and neoplasms in the context of Carney complex (CNC) and in isolated cases, such as in primary pigmented nodular adrenocortical disease (PPNAD), cortisol-producing adrenal adenomas (CPAs), and various cancers. PRKAR1A mutations have been found in subjects with impaired cAMP-dependent signaling and skeletal defects; bone tumors also develop in both humans and mice with PKA abnormalities. We studied the PRKACB gene in 148 subjects with PPNAD and related disorders, who did not have other PKA-related defects and identified two subjects with possibly pathogenic PRKACB gene variants and unusual bone and endocrine phenotypes. The first presented with bone and other abnormalities and carried a de novo c.858_860GAA (p.K286del) variant. The second subject carried the c.899C>T (p.T300M or p.T347M in another isoform) variant and had a PPNAD-like phenotype. Both variants are highly conserved in the PRKACB gene. In functional studies, the p.K286del variant affected PRKACB protein stability and led to increased PKA signaling. The p.T300M variant did not affect protein stability or response to cAMP and its pathogenicity remains uncertain. We conclude that PRKACB germline variants are uncommon but may be associated with phenotypes that resemble those of other PKA-related defects. However, detailed investigation of each variant is needed as PRKACB appears to be only rarely affected in these conditions, and variants such as p.T300M maybe proven to be clinically insignificant, whereas others (such as p.K286del) are clearly pathogenic and may be responsible for a novel syndrome, associated with endocrine and skeletal abnormalities.